Artisanal Fishing in Kerala Backwaters: A Socioeconomic Assessment of Indian Coracles - M. Ramees Rahman; Solly Solomon; N. R. Athira and S. Manomi (Asian Journal of Agricultural Extension, Economics & Sociology, 2017)
While considering pollution and economic losses caused by modern fishing systems/fleet to natural environment, traditional fishing techniques have its own relevance as a sustainable way of harvesting systems with least negative impact to the fishing environment. The study focuses on an economic analysis of one of the major time-tested methods of sustainable fishing, ‘Indian coracles’, operated in the Vembanad backwaters of Kerala. An exploratory study was conducted among the migrated coracle fishers operating in the ‘’Kochi Kaayal’’ area of Vembanad estuary, Ernakulam district, Kerala during February – May, 2017. Primary data was collected from 15 coracle fishers selected randomly, which cover around 75 per cent of total migrant coracle fishers operating in the area. Fishers were personally interviewed by using a well-structured interview schedule. Major parameters considered include personal as well as family details, education status, income details, asset particulars, savings, indebtedness, expenditure pattern, details of migration, reasons for migration, problems during migration, and major socio-economic achievements through migration. The Garrette ranking method and other major econometric tools were used to analyze the problems of, and reasons for, their migration, as well as fishing operation. It was observed that disguised unemployment and competition prevailing in their native place are the major reasons for migration to Kerala coast decades ago. Fishers achieved betterment in socioeconomic conditions with their migration to the Kerala coast. Also, the fishing technique is found to be eco-friendly and hence relevant as a sustainable fishing technique. Immense scope of tourism as well as the significance of spreading awareness among the local fishermen about coracle fishing as a sustainable fishing technique, is highlighted in the study. Present study is relevant as the first of its kind done in the area and in the technique.